Chapter Concluding Remarks - Destrooper, Tine (Taylor & Francis, 2023)
This chapter concludes the volume, drawing together its different theoretical and empirical chapters. It argues that there is merit in looking beyond paradigmatic transitional contexts, since such a focus allows transitional justice to become relevant for a variety of justice actors, enables a decolonization of the field, and offers a new perspective on what can be expected of transitional justice. To make this argument the chapter discusses five themes that surface in the empirical chapters describing when transitional justice travels to aparadigmatic cases: 1. Pluralism and the unsettled character of transitional justice. 2. The standardisation of localized justice initiatives. 3. Ongoing transitions. 4. Political will and legitimacy. 5. Bridging the divide between scholars and practitioners. These five themes help to understand the contemporary field of transitional justice as it has expanded from transitional to non-transitional, aparadigmatic contexts.